Analisis Sistem Pengendalian Piutang Terhadap Piutang Tak Tertagih pada PT. Abadi Sakti Mitra Mandiri - Ayu, Retno (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
Uncollectible accounts are one of the causes of losses in the company because they can hinder the process of entering finance into the company. Required control of good accounts receivable so that the company does not experience losses. This study aims to determine the application of a COSO-based internal control system for accounts receivable at PT. Abadi Sakti Mitra Mandiri. The method used in this study uses a grounded research approach. Grounded research is a research method on facts and uses comparative analysis with the aim of establishing concepts, proving theories, and developing theories, collecting, and analyzing data at the same time. Based on the results of research conducted, the internal control system implemented by PT. Abadi Sakti Mitra Mandiri has not been good enough. This is indicated by the increase in the level of bad debts caused by the low level of internal control in the elements of control activity, namely the existence of multiple jobs so that the risk assessment in the provision of receivables becomes ineffective. Therefore, it is necessary to have additional employees in marketing and selling products as well as a special section for the analysis of receivables, so that the receivables control process can run effectively and efficiently. The company should also provide fines to customers who delay payment of their receivables.